2017
DOI: 10.1002/mp.12405
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Ion chamber angular dependence in a magnetic field

Abstract: Within a magnetic field-oriented orthogonal to the radiation beam, the ionization chamber dose-response fluctuates greatly as a function of polar and azimuthal angle, where a parallel field yields a more homogeneous dose-response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…The statistical uncertainty on all of these difference is about 0.14%. These results are in agreement with the findings of Reynolds et al., in which a 3° misalignment in any direction about the the 90° and 270° orientations produced a maximum variation in dose of roughly 1% and an average variation of about 0.5%. Furthermore, although slightly larger ΔkQmagfalse(italicθfalse) values are observed for 0° and 180° in Table , the advantage of nearly completely eliminating the effect of the sensitive volume on kQitalicmag, as compared to the 90° and 270° simulations, and the absence of a difference between the kQitalicmag values at 0 and 180°, as described in Section 3.A, makes the C‐I and C‐III orientations the ideal orientations for ion chamber dosimetry in magnetic fields.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The statistical uncertainty on all of these difference is about 0.14%. These results are in agreement with the findings of Reynolds et al., in which a 3° misalignment in any direction about the the 90° and 270° orientations produced a maximum variation in dose of roughly 1% and an average variation of about 0.5%. Furthermore, although slightly larger ΔkQmagfalse(italicθfalse) values are observed for 0° and 180° in Table , the advantage of nearly completely eliminating the effect of the sensitive volume on kQitalicmag, as compared to the 90° and 270° simulations, and the absence of a difference between the kQitalicmag values at 0 and 180°, as described in Section 3.A, makes the C‐I and C‐III orientations the ideal orientations for ion chamber dosimetry in magnetic fields.…”
Section: Resultssupporting
confidence: 93%
“…The statistical uncertainty on all of these difference is about 0.14%. These results are in agreement with the findings of Reynolds et al, 17 in which a 3°misalignment in Table III, the advantage of nearly completely eliminating the effect of the sensitive volume on k mag Q , as compared to the 90°and 270°simulations, and the absence of a difference between the k mag Q values at 0 and 180°, as described in Section 3.A, makes the C-I and C-III orientations the ideal orientations for ion chamber dosimetry in magnetic fields. Additionally, as is seen in the Dk mag Q ðh; DVÞ results, Table III, in these orientations the lack of variation in k mag Q demonstrates that the details of the sensitive volume are negligible (as compared to several percent change due to sensitive volume changes in the C-II and C-IV orientations).…”
Section: B Sensitive Volume Effectssupporting
confidence: 94%
See 1 more Smart Citation
“…In addition to these challenges, all quality assurance equipment must be MR compatible, and the impact of the magnetic field on the response of the QA equipment including ion chambers must be well characterized. [14][15][16][17][18] The characterization of a research version of the Monaco treatment planning system (TPS) 19 and the commissioning of the MRI scanner using research MR sequences that are not widely available have been previously reported. 20 Despite these initial efforts, there is little published guidance on commissioning the Elekta Unity in its current FDA-approved state.…”
mentioning
confidence: 99%
“…Using a δ u of 0.02 or smaller has become common for Monte Carlo simulations which use similar theories 19,20,40,77 , but this produces a potentially severe increase in computational time. The solution for a dose calculation in the presence of a magnetic field is expected to converge as δ u decreases, and determining the largest possible δ u that does not cause variations in the solution is required to improve efficiency.…”
Section: Lorentz Force In a Condensed History Calculationmentioning
confidence: 99%